Visualizing the miraculous, visualizing the sacred : evangelization and the "cultural war" in sixteenth century Mexico - Jackson, Robert H. (Robert Howard) (Cambridge Scholars Publishing, 2014)
French historian Robert Ricard postulated a quick and facile evangelization of the native populations of central Mexico. However, evidence shows that native peoples incorporated Catholicism into their religious beliefs on their own terms, and continued to make sacrifices to their traditional deities. In particular the deities of rain (Tlaloc and Dzahui) and the fertility of the soil (Xipe Totec) continued to be important following the conquest and the beginning of the so-called "spiritual conquest." This study examines visual evidence of the persistence of traditional religious practices, including embedded pre-hispanic stones placed in churches and convents, and pre-hispanic iconography in what ostensibly were Christian murals